Mitigating anthropogenic climate change with aqueous green energy - Sophia T. Olim; Anna Nickoloff; Leslie J. Moffat; Andrew J. Weaver; Michael Eby (Scientific Reports)
Abstract Reaching net zero emissions and limiting global warming to 2 °C requires the widespread introduction of technology-based solutions to draw down existing atmospheric levels and future emissions of CO2. One such approach is direct air CO2 capture and storage (DACCS), a readily available, yet energy-intensive process. The combination of DACCS and ocean thermal energy conversion (OTEC) allows for independently powered carbon capture plants to inject concentrated carbon into deep marine sediments where storage is generally safe and permanent. OTEC is a form of electricity production that exploits the temperature difference between deep and shallow ocean waters, and can power DACCS on floating platforms at a price competitive with coal-generated electricity. Here we highlight the scale of the challenge facing society. We show that a safe and sustainable level of OTEC-generated electricity powering DACCS for 70 years could result in up to a 35% decrease in the relative global mean temperature warming compared to a business-as-usual emissions scenario.